Pharmacologic Stress Gastropathy Prophylaxis May Not Be Necessary in At-Risk Surgical Trauma ICU Patients Tolerating Enteral Nutrition. (July 2018) - Palm, Nicole M.; McKinzie, Brian; Ferguson, Pamela L.; Chapman, Emily; Dorlon, Margaret; Eriksson, Evert A.; Jewett, Brent; Leon, Stuart M.; Privette, Alicia R.; Fakhry, Samir M.
Objective: Stress gastropathy is a rare complication of the intensive care unit stay with high morbidity and mortality. There are data that support the concept that patients tolerating enteral nutrition have sufficient gut blood flow to obviate the need for prophylaxis; however, no robust studies exist. This study assesses the incidence of clinically significant gastrointestinal bleeding in surgical trauma intensive care unit (STICU) patients at risk of stress gastropathy secondary to mechanical ventilation receiving enteral nutrition without pharmacologic prophylaxis. Design: A retrospective cohort study of records from 2008 to 2013. Setting: Adult patients in a single-center STICU were included. Patients: Patients were included if they received full enteral nutrition while on mechanical ventilation. Exclusion criteria were coagulopathy, glucocorticoid use, prior-to-admission acid-suppressive therapy use, direct trauma or surgery to the stomach, failure to tolerate goal enteral nutrition, orders to allow natural death, and deviation from the intervention. Intervention: Pharmacologic stress ulcer prophylaxis was discontinued once enteral nutrition was providing full caloric requirements for patients requiring mechanical ventilation. Measurements and Main Results: A total of 200 patients were included. The median age was 42 years, 83.0% were male, and 96.0% were trauma patients. The incidence of clinically significant gastrointestinal bleeding was 0.50%, with a subset analysis of traumatic brain injury patients yielding an incidence of 0.68%. Rates of ventilator-associated pneumonia and Clostridium difficile infection were low at 1.0 case/1000 ventilator days and 0.2 events/1000 patient days, respectively. Hospital all-cause mortality was 2.0%. Cost savings of US$121/patient stay were realized. Conclusion: Stress gastropathy is rare in this population. Surgical and trauma patients at risk for stress gastropathy did not benefit from continued pharmacologic prophylaxis once they tolerated enteral nutrition. Pharmacologic prophylaxis may safely be discontinued in this patient population. Further investigation is warranted to determine whether continued prophylaxis after attaining enteral feeding goals is detrimental.